Factor XII and Other Hemostatic Protein Abnormalities in Nephrotic Syndrome Patients - Thompson, Arthur R (Thrombosis and Haemostasis, 1982)
Factor XII clotting activities and antigen levels were assayed in 14 plasma samples from 10 patients with nephrotic syndrome; the group was heterogeneous clinically and histologically. Factor XII was low at initial sampling in 7 of the 10 patients; in 7 of the 14 samples, factor XII antigen was in excess over clotting activity. Inhibition of factor XII could not be demonstrated; excess plasma antigen and urinary antigen (when present) had normal patterns on crossed-immunoelectrophoresis, indicating no major changes in charge or size. In 3 patients tested more than once, plasma levels of factor XII were increased up to 6fold in steroid-induced remission.Of other hemostatic factors assessed for comparison, factor VIII was elevated in 11 of the 14 samples; eight of these had elevated factor VII levels as well. Eight samples from six patients showed low antithrombin III levels; one of these patients had recurrent thromboses. Antithrombin III levels correlated with the serum albumin concentration.Only two of the eight urines tested had detectable factor XII antigen; a third had factor IX and prothrombin and no factor XII. Plasminogen and antithrombin III were readily demonstrated in all urine samples with higher concentrations in those patients with less selective proteinuria. Urinary and plasma levels were not correlated, suggesting that increased consumption or turnover was not simply related to increased filtration.
Keywords: Nephrotic syndrome; Hemostasis; Factor XII